2014
DOI: 10.1007/s40273-014-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Cost-Effectiveness Analyses for the Treatment of Chronic Lymphocytic Leukaemia: A Review of Methods to Model Disease Outcomes and Estimate Utility

Abstract: Assessing the economic value of treatments for chronic lymphocytic leukaemia (CLL) is necessary to support healthcare decision makers; however, it poses a number of challenges. This paper reviews economic models of CLL treatment to learn the lessons from this experience and support ongoing model efforts. A search of databases and submissions to key health technology assessment agencies identified nine models. The modelling approaches adopted across these studies were fairly similar, with most models adopting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
5
0
2
Order By: Relevance
“…Em adição a isso, a metodologia simples de modelagem com três estados de saúde pode representar uma forma limitante de refletir uma doença crônica, uma vez que, em um período de lifetime, o paciente pode apresentar outros estados de saúde, além de sofrer influências de linhas posteriores de tratamento. A ausência de dados que apresentem o acompanhamento de pacientes em todas as fases da doença também é um fator que dificulta as estimativas de desfechos clínicos para avaliações econômicas (Marsh, et al, 2014).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em adição a isso, a metodologia simples de modelagem com três estados de saúde pode representar uma forma limitante de refletir uma doença crônica, uma vez que, em um período de lifetime, o paciente pode apresentar outros estados de saúde, além de sofrer influências de linhas posteriores de tratamento. A ausência de dados que apresentem o acompanhamento de pacientes em todas as fases da doença também é um fator que dificulta as estimativas de desfechos clínicos para avaliações econômicas (Marsh, et al, 2014).…”
Section: Discussionunclassified
“…Mesmo na ausência de informações a longo prazo, a maioria dos estudos com modelos econômicos para LLC adota o mesmo formato de modelagem do presente estudo, e foi e é aceita por agências de tecnologia de saúde internacionais (Marsh et al, 2014). A utilização de análise de custo-efetividade auxilia na comparação tanto de desfechos clínicos quanto de desfechos econômicos de duas intervenções, além de serem ferramentas importantes e úteis durante a tomada de decisão de fontes pagadoras, principalmente em um contexto de recursos econômicos limitados.…”
Section: Discussionunclassified
“…Although we used a cohort Markov model for analyzing costeffectiveness-as endorsed by NICE in the United Kingdomsimilar previous analyses in patients with CLL have shown that there are some uncertainties associated with this approach [31]. In this respect, patients in the CLL11 trial that we included in our analysis continue to be followed up.…”
Section: Discussionmentioning
confidence: 99%
“…The model utilized a Markov process, which is the standard method used in cost-effectiveness studies to represent the natural history in various diseases 33 , 34 and the most widely used model for analyzing cost-effectiveness in CLL. 35 …”
Section: Discussionmentioning
confidence: 99%